PANELIZED ELECTRICAL POWER OUTPUT MONITORING SYSTEM INTEGRATED SOLAR WEB SERVER - Aripriharta, Aripriharta; Aprilia Putri , Annisa Firly; Afandi, Arif Nur; Omar, Saodah; Faiz, Mohamad Rodhi (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2024)
In Indonesia, the duration of sunlight energy harvesting is around 7-8 hours perday. It is considered capable of generating electricity with photovoltaics (PV). Proper monitoring of solar panels can help identify and fix problems with solar panels. To overcome these problems, this research will develop a solar panel electrical power output monitoring system integrated with a Web Server using the Internet of Things that allows users to perform remote monitoring via smartphones and PCs. The method used in this research is the DevOps method. The results showed that the monitoring system of solar panel electrical power output integrated with Web Server runs well and can display data in real-time with a delay time of ± 0.50 ms. Furthermore, overall system testing was carried out from 08.00 to 16.00 with the maximum voltage and current generated of 5.13V and 0.176A. The efficiency value produced by the 10Wp solar panel is 94.16%.